Der implizite Lerner in multimedialen Lernarrangements - Kremer, H.-Hugo; Sloane, Peter F. E. (Kölner Zeitschrift für Wirtschaft und Pädagogik)

Towards Quality of Service for Parallel Computing: An Overview of the MILAN Project - Karl, Holger (High-Performance Computing and Networking, 7th International Conference, HPCN Europe 1999, Amsterdam, The Netherlands, April 12-14, 1999, Proceedings)

Coscheduling through Synchronized Scheduling Servers -- A Prototype and Experiments - Karl, Holger (Parallel and Distributed Processing, 11 IPPS/SPDP'99 Workshops Held in Conjunction with the 13th International Parallel Processing Symposium and 10th Symposium on Parallel and Distributed Processing, San Juan, Puerto Rico, USA, April 12-16, 1999, Proceedings)

Schwingungsanalyse von vorgespannten Schaufeln mit Deckplatten im Schaufelkranz - Popp, Karl; Sextro, Walter (Forschungsvereinigung Verbrennungskraftmaschinen (FW) -lnformationstagung Turbinen)

Experimental verification of a non-Hertzian contact model - Sextro, Walter (International conference on computational methods in contact mechanics)

Forced Vibration of Elastic Structures with Friction Contacts - Sextro, Walter (ASME Design Engineering Technical Conferences)

Ein ebenes Reibkontaktmodell zur Berechnung von Schaufelschwingungen mit Reibelementen - Sextro, Walter; Popp, Karl (Zeitschrift für angewandte Mathematik und Mechanik (ZAMM))

Schwingungsanalyse von vorgespannten Schaufeln mit Deckplatten im Schaufelkranz - Sextro, Walter; Popp, Karl (Forschungsvereinigung Verbrennungskraftmaschinen (FW))

Financial Participation in Europe: Determinants and Outcomes - Festing, M; Groening, Y; Kabst, Rüdiger (Economic and Industrial Democracy.)

Layout for a wind-power-driven, reverse osmosis installation for desalting brackish water in operation on an island - Bendfeld, Jörg; Bettenwort, Gerd; Ortjohann, Egon; Voss, Jürgen (Proceedings of the 1999 European Wind Energy Conference, 1-5 March 1999 Nice, France, pp975-978)

Hanif Kureishi. My Beautiful Laundrette

British Literature and Culture. Divergent Views and Attitudes. On the Occasion of Gerd Stratmann's 60th Birthday

Shortest-Path Routing in Arbitrary Networks - Meyer auf der Heide, Friedhelm; Vöcking, Berthold (Journal of Algorithms)

Allocating Weighted Jobs in Parallel - Berenbrink, P.; Meyer auf der Heide, Friedhelm; Schröder, K. (Theory of Computing Systems)

The computation of lyapunov exponents via spatial integration with application to blowout bifurcations - Aston, Philip J.; Dellnitz, Michael (Computer Methods in Applied Mechanics and Engineering)

On the Approximation of Complicated Dynamical Behavior - Dellnitz, Michael; Junge, Oliver (SIAM Journal on Numerical Analysis)

Computation of Essential Molecular Dynamics by Subdivision Techniques - Deuflhard, Peter; Dellnitz, Michael; Junge, Oliver; Schütte, Christof (Computational Molecular Dynamics: Challenges, Methods, Ideas)

Das neue europäische Schadenersatzrecht - Krimphove, Dieter (Österreichische Juristenzeitschrift (ÖJZ))

Ein Internet-Client für ein Geo-Informationssystem zur Visualisierung geowissenschaftlicher Daten - Lenz, C.; Stüwe, J.D.; Domik, Gitta; Gaulke, J.

Visualizing Complicated Dynamics - Bürkle, David; Dellnitz, Michael; Junge, Oliver; Rumpf, Martin; Spielberg, Michael (Proceedings of Visualization 99)

International Workshop on Communication and Data Management in Large Networks - Mayr, E. W.; Meyer auf der Heide, Friedhelm; Wanka, Rolf (Informatik aktuell)

Provably Good and Practical Strategies for Non-uniform Data Management in Networks - Meyer auf der Heide, Friedhelm; Vöcking, Berthold; Westermann, Matthias (Algorithms - ESA’ 99)

An Economic Analysis of the Law of Good-Faith Purchase in European Property Law - Krimphove, Dieter (Gdanskie Strudia Prawnicze)

The Philips/RWTH system for transcription of broadcast news - Beyerlein, Peter; Aubert, Xavier L.; Haeb-Umbach, Reinhold; Harris, Matthew J.; Klakow, Dietrich; Wendemuth, Andreas; Molau, Sirko; Pitz, Michael; Sixtus, Achim (Eurospeech)
This paper contains a description of the Philips/RWTH 1998 HUB4 system which has been build in a joint e ort of Philips Research Laboratories Aachen and Aachen University of Technology. We will focus our discussion on recent improvements compared to the original 1997 HUB4 system and evaluate them on the HUB4'97 evaluation data. The paper will deal with 1. a rough system overview including feature extraction, acoustic training, audio stream segmentation, and decoding 2. log-linear interpolation of distance-language models, 3. and the integration of various acoustic and language models via Discriminative Model Combination (DMC). The performance of the described system is 23% (relative) better than the performance of the 1997 Philips HUB4 system. A word error rate of 17.9% was achieved on the 1997 HUB4 evaluation set, compared to 23.5% using the original 1997 system.

The Philips/RWTH System for Transcription of Broadcast News - Beyerlein, Peter; Aubert, Xavier L.; Haeb-Umbach, Reinhold; Harris, Matthew J.; Klakow, Dietrich; Wendemuth, Andreas; Molau, Sirko; Pitz, Michael; Sixtus, Achim (Broadcast News Transcription and Understanding Workshop, Washington)
This paper contains a description of the Philips/RWTH 1998 HUB4 system which has been build in a joint e ort of Philips Research Laboratories Aachen and Aachen University of Technology. We will focus our discussion on recent improvements compared to the original 1997 HUB4 system and evaluate them on the HUB4'97 evaluation data. The paper will deal with 1. a rough system overview including feature extraction, acoustic training, audio stream segmentation, and decoding 2. log-linear interpolation of distance-language models, 3. and the integration of various acoustic and language models via Discriminative Model Combination (DMC). The performance of the described system is 23% (relative) better than the performance of the 1997 Philips HUB4 system. A word error rate of 17.9% was achieved on the 1997 HUB4 evaluation set, compared to 23.5% using the original 1997 system.

Investigations on inter-speaker variability in the feature space - Haeb-Umbach, Reinhold (ICASSP99 Phoenix, AZ)
We apply Fisher variate analysis to measure the effectiveness of speaker normalization techniques. A trace criterion, which measures the ratio of the variations due to different phonemes compared to variations due to different speakers, serves as a first assessment of a feature set without the need for recognition experiments. By using this measure and by recognition experiments we demonstrate that cepstral mean normalization also has a speaker normalization effect, in addition to the well-known channel normalization effect. Similarly vocal tract normalization (VTN) is shown to remove inter-speaker variability. For VTN we show that normalization on a per sentence basis performs better than normalization on a per speaker basis. Recognition results are given on Wall Street Journal and Hub-4 databases

An Investigation of Cepstral Parameterisations for Large Vocabulary Speech Recognition - Haeb-Umbach, Reinhold; Loog, Marco (Eurospeech)
We examined variants of MFCC and PLP cepstral parameterisations in the context of large vocabulary continuous speech recognition under different acous-tical environmental conditions: Compared to MFCC, mel-frequency PLP uses a cubic root intensity-to-loudness law, and an LPC analysis is applied to the mel-warped spectrum. In LPC-smoothed MFCC, the only difference to MFCC is the additional LPC smoothing of the warped spectrum. While neither technique was able to significantly outperform the MFCC parameterisation in our setup which includes an LDA feature transformation, feature set combination via DMC at the acoustic likelihood level and via ROVER at the recognized word level delivered small but consistent improvements.

A study of broadcast news audio stream segmentation and segment clustering - Harris, Matthew J.; Aubert, Xavier L.; Haeb-Umbach, Reinhold; Beyerlein, Peter (Eurospeech)
In transcription of broadcast news, dividing the signal into homogeneous segments, and clustering together similar segments is important. Decoding a complete broadcast news program in one chunk is technically di cult. Also, through creation of homogeneous clusters of segments, improvement from adaptation can be increased. Two systems of segmentation and clustering are compared. The best system used the BIC algorithm to produce long, homogeneous segments, and a nearest neighbour bottom-up agglomerative clustering algorithm to produce homogeneous clusters. Adaptation brought a word error rate (WER) improvement from 23:4% to 21:0% using the automatic segmentation and clustering, compared to an improvement from 21:8% to 20:0% using a handmade \correct" segmentation and clustering.

Kooperative Arbeitsplattformen - CSCW-Systeme in Lehr- und Lernkontexten - Schulte, Carsten; Selke, Harald; Huth, Carsten (LOG IN)

Dekonstruktion von Informatiksystemen als Unterrichtsmethode - Zugang zu objektorientierten Sichtweisen im Informatikunterricht - Hampel, Thorsten; Magenheim, Johannes; Schulte, Carsten (INFOS)

Fuzzy rules in case-based reasoning - Hüllermeier, Eyke; Dubois, D.; Prade, H. (In Proceedings RàPC-1999, Raisonnement à partir de Cas, Paris Palaiseau, France, In Conferences AFIA-1999)

Some New Aspects of Neoclassical Investment Theory with Taxes - König, Rolf; Sureth-Sloane, Caren

Toward a probabilistic formalization of case-based inference - Hüllermeier, Eyke (in Proceedings IJCAI-99, 16th international Joint Conference on Artificial Intelligence, Stockholm, Sweden)

Exploiting similarity for supporting data analysis and problem solving - Hüllermeier, Eyke (In Proceedings IDA-1999, 3th International Symposium on Intelligent Data Analysis, Amsterdam, Netherlands)

Extensions of a qualitative approach to case-based decision making: Unvertainty and fuzzy quantification in act evaluation - Hüllermeier, Eyke; Dubois, D.; Prade, H. (in Proceedings EUFIT-99 7th European Congress on Intelligent Techniques and Soft Computing, Aachen, Germany)

Toward models of case-based decision making - Hüllermeier, Eyke (in Proceedings EUFIT-99 7th European Congress on Intelligent Techniques and Soft Computing, Aachen, Germany)

A possibilistic formalization of case-based reasoning and decision making - Hüllermeier, Eyke (in Proceedings of the 6th International Conference on Computational Intelligence, Dortmund, Germany)

Aktuelle Rechtsfragen des Börsentermin- und Optionshandels -Anforderungen an Bank und Kunde- - Krimphove, Dieter

Numerical methods for fuzzy initial value problems - Hüllermeier, Eyke (International Journal of Uncertainty, Fuzziness and Knowledge-Based Systems)

Approximation of uncertain funtional relationships - Hüllermeier, Eyke (Fuzzy Sets and Systems)

Qualitatives Schließen und Qualitative Simulation - Hüllermeier, Eyke (Modellierung, Simulation und Künstliche Intelligenz)

Selbsttestbare Steuerwerke - Strukturen und Syntheseverfahren - Hellebrand, Sybille

Exploiting Symmetries to Speed Up Transparent BIST - Hellebrand, Sybille; Wunderlich, Hans-Joachim; N. Yarmolik, Vyacheslav
Keywords: WORKSHOP

Counterexamples to a conjecture about Petersen-minors in supersnarks - Steffen, Eckhard (Discrete Mathematics)

Non-bicritical critical snarks - Steffen, Eckhard (Graphs Comb.)

Cyclically 5-edge connected non-bicritical critical snarks - Grünewald, Stefan; Steffen, Eckhard (Discuss. Math. Graph Theory)

Chromatic-index-critical graphs of even order - Grünewald, Stefan; Steffen, Eckhard (J. Graph Theory)

Dynamic circuit generation for Boolean satisfiability in an object-oriented design environment - Mencer, Oskar; Platzner, Marco (Proceedings of the 32nd Annual Hawaii International Conference on Systems Sciences (HICSS-32))

Communication Synthesis for Reconfigurable Embedded Systems - Eisenring, Michael; Platzner, Marco; Thiele, Lothar (Proceedings of the 9th International Workshop on Field Programmable Logic and Applications (FPL))

Ab initio calculation of linear and nonlinear optical properties of semiconductor structures - Bechstedt, F.; Adolph, B.; Schmidt, Wolf Gero (Brazilian Journal of Physics)

SELF-ENERGY EFFECTS IN THE OPTICAL ANISOTROPY OF GaP(001) - Schmidt, Wolf Gero; FATTEBERT, J. L.; BERNHOLC, J.; BECHSTEDT, F. (Surface Review and Letters)
We calculate the reflectance anisotropy for GaP(001)(2×4) surfaces using a real-space multigrid method and ab initio pseudopotentials. Our results obtained within DFT-LDA show good qualitative agreement with recent experiments. This holds in particular for the stoichiometric trends. A strong negative anisotropy at low photon energies is linked to the formation of Ga–Ga bonds along the [110] direction. There are discrepancies, however, with respect to the line shape and the energetic positions of characteristic peaks. Substantial improvement is achieved by using a numerically efficient GW approach with approximations for local-field effects and dynamical screening. We find that the spectral features related to transitions between surface perturbed bulk wave functions are more strongly affected by self-energy corrections than anisotropies directly linked to surface electronic states.

Theoretical Aspects of the Optical Response of Semiconductor Surfaces - Bechstedt, F.; Pulci, O.; Schmidt, Wolf Gero (physica status solidi (a))

GaP(001) and InP(001): Reflectance anisotropy and surface geometry - Esser, N.; Schmidt, Wolf Gero; Bernholc, J.; Frisch, A. M.; Vogt, P.; Zorn, M.; Pristovsek, M.; Richter, W.; Bechstedt, F.; Hannappel, Th.; Visbeck, S. (Journal of Vacuum Science & Technology B: Microelectronics and Nanometer Structures)

(2×4)GaP(001) surface: Atomic structure and optical anisotropy - Frisch, A. M.; Schmidt, Wolf Gero; Bernholc, J.; Pristovsek, M.; Esser, N.; Richter, W. (Physical Review B)

Structural fingerprints in the reflectance anisotropy spectra ofInP(001)(2×4)surfaces - Schmidt, Wolf Gero; Briggs, E. L.; Bernholc, J.; Bechstedt, F. (Physical Review B)

Disziplinen im Kontext. Perspektiven der Disziplingeschichtsschreibung
Rezensionen: J. Westerhoff, „Ein Sammelband zur Methodologie der Disziplingeschichte“, http://www.literaturkritik.de/txt/2000-04-81.html; Philosophischer Literaturanzeiger 54 (2001), 265–272 (R. Piston).

Operation of a three-phase/three-level-rectifier in wide range and single-phase applications - Ide, P.; Froehleke, N.; Grotstollen, H.; Korb, W.; Margaritis, B. (IECON'99. Conference Proceedings. 25th Annual Conference of the IEEE Industrial Electronics Society (Cat. No.99CH37029))

Design of extended Kalman filters for high performance position control of electrical drives - Beineke, S.; Wertz, H. (1999 IEEE/ASME International Conference on Advanced Intelligent Mechatronics (Cat. No.99TH8399))

High performance speed control for ultrasonic motors - Maas, J.; Schulte, T. (1999 IEEE/ASME International Conference on Advanced Intelligent Mechatronics (Cat. No.99TH8399))

Abduktion und Heuristik - Peckhaus, Volker (Rationalität, Realismus, Revision.Vorträge des 3. Internationalen Kongresses der Gesellschaft für Analytische Philosophie)

Philosophie im Wissenskontext. Von der Unverzichtbarkeit historischer Philosophiegeschichtsschreibung - Peckhaus, Volker (Wege der Vernunft. Philosophieren zwischen Tätigkeit und Reflexion)

Chancen kontextueller Disziplingeschichtsschreibung in der Mathematik - Peckhaus, Volker (Diszilinen im Kontext. Perspektiven der Disziplingeschichtsschreibung)

Moral Integrity during a Difficult Period: Beth and Scholz - Peckhaus, Volker (Philosophia Scientiae (Nancy) 3 (4) (1998/1999) Themenheft: Un logicien consciencieux. La philosophie de Evert Willem Beth)

19th Century Logic: Between Philosophy and Mathematics - Peckhaus, Volker (Proceedings of the Canadian Society for the History and Philosophy of Mathematics. Société Canadienne d’Histoire et Philosophie des Mathématiques, Bd. 11: Twenty-Fourth Annual Meeting. University of Ottawa. Ottawa, Ontario, May 29–31, 1998)

Computer aided commissioning of speed and position control for electrical drives with identification of mechanical load - Wertz, H.; Beineke, S.; Fröhleke, N.; Bolognani, S.; Unterkofler, K.; Zigliotto, M.; Zordan, M. (Conference Record of the 1999 IEEE Industry Applications Conference. Thirty-Forth IAS Annual Meeting (Cat. No.99CH36370))

Computer aided investigation of the auxiliary resonant commutated pole converter for wide range applications such as welding power supplies - Fröhleke, N.; Pieper, R.; Mundinger, H.; Grotstollen, H. (IECON'99. Conference Proceedings. 25th Annual Conference of the IEEE Industrial Electronics Society (Cat. No.99CH37029))

Martin Kusch, Psychologism. A Case Study in the Sociology of Philosophical Knowledge. (Philosophical Issues in Science) London/New York: Routledge 1995 - Peckhaus, Volker (Berichte zur Wissenschaftsgeschichte)

Gunter Scholtz (Hrsg.): Historismus am Ende des 20. Jahrhunderts. Eine Internationale Diskussion. Akademie-Verlag, Berlin 1997 - Peckhaus, Volker (Philosophischer Literaturanzeiger)

Ansgar Beckermann, Einführung in die Logik. Walter de Gruyter, Berlin/New York, 1997 (Sammlung Göschen; 2243) - Peckhaus, Volker (Zeitschrift für allgemeine Wissenschaftstheorie)

On Deepening Foundations: Hilbert’s Axiomatic Program between Pragmatics and Naturalism [Abstract] - Peckhaus, Volker (International Union of History and Philosophy of Science. 11th International Congress of Logic, Methodology and Philosophy of Science. Volume of Abstracts. August 20–26, 1999, Cracow, Poland)

Mathematische vs. Axiomatische Methode [Abstract] - Peckhaus, Volker (Deutsche Mathematiker-Vereinigung. Jahrestagung 1999. 5.–11. September an der Johannes Gutenberg-Universität in Mainz. Programm)

Hugh MacColl and the German Algebra of Logic - Peckhaus, Volker (Nordic Journal of Philosophical Logic)
1998, erschienen im Dezember 1999 Auszug aus Abstract: Zbl. Math. 939.01008; MR 2001a:03001.

19th Century Logic: Between Philosophy and Mathematics (Wiederabdruck und Online-Fassung) - Peckhaus, Volker (The Bulletin of Symbolic Logic)
Rezension: Zbl. Math. 941.03002 (R. Murawski); MR 2001j:01030 (J.W. Dauben).

Selbsteinstellender Antrieb mit drehmomentoptimal betriebenem Asynchronmotor - Bünte, Andreas

Прагмастилистические функции фразеологических модификаций в тексте [Pragmastilistische Funktionen phraseologischer Modifikationen im Text – russ.] - Ptashnyk, Stefaniya (: Сборник материалов международной языковедческой конференции «Проблемы семантического описания единиц языка и речи», Минск, 10–12.11.1998)

Agnieszka Fraczek: Zur Geschichte der deutsch-polnischen und polnisch-deutschen Lexikographie (1772-1868) - Ptashnyk, Stefaniya (Studia Germa-nica Gedanensia 9. Gdansk, 2001. Jaroszewski, Marek (Hrsg.))

Universality of the Hohenberg–Kohn functional - Schindlmayr, Arno (American Journal of Physics)

Falk, P. / C. Campbell (Hg.): The Shopping Experience, 1997 - Tönnies, Merle (Journal for the Study of British Cultures)

Becker, J.: Nicht-Ich-Identität. Ästhtische Subjektivität in Samuel Becketts Arbeiten für Theater, Radio, Film und Fernsehen, 1998 - Tönnies, Merle (Forum Modernes Theater)

Ledger, S.: The New Woman. Fiction and Feminism at the 'Fin de Siècle', 1997 - Tönnies, Merle (Anglia)

Andreas Riem und die Französische Revolution - Süßmann, Johannes (Andreas Riem. Ein Europäer aus der Pfalz)

Parameter identification of ultrasonic motors - Schulte, T.; Fröhleke, N. (1999 IEEE/ASME International Conference on Advanced Intelligent Mechatronics (Cat. No.99TH8399))

Error Detecting Refreshment for Embedded DRAMs - Hellebrand, Sybille; Wunderlich, Hans-Joachim; A. Ivaniuk, Alexander; V. Klimets, Yuri; N. Yarmolik, Vyacheslav (17th IEEE VLSI Test Symposium (VTS'99))

Transparent Word-Oriented Memory BIST Based on Symmetric March Algorithms - N. Yarmolik, Vyacheslav; V. Bykov, Iuri; Hellebrand, Sybille; Wunderlich, Hans-Joachim (Third European Dependable Computing Conference (EDCC-3))

Symmetric Transparent BIST for RAMs - Hellebrand, Sybille; Wunderlich, Hans-Joachim; N. Yarmolik, Vyacheslav (Design Automation and Test in Europe (DATE'99))

“Rehabilitation der Sinnlichkeit”? Neuere Arbeiten über das Verhältnis von Anthropologie und Ästhetik im 18. Jahrhundert - van Laak, Lothar (Sprache und Literatur in Wissenschaft und Unterricht 83)

Schwichtenberg, Helmut, “Density and Choice for Total Continuous Functions”, in P. Odifreddi (ed.), Kreiseliana, Wellesley, MA 1996 [Zbl 0894.03002], 335–362. Peters: Wellesley, MA 1996 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Gert Hübner, Frauenpreis. Studien zur Funktion der laudativen Rede in der mittelhochdeutschen Minnekanzone, Baden-Baden 1996 - Egidi, Margreth (Arbitrium 1999, H. 2)

v. Helmholtz, "Hermann, Schriften zur Erkenntnistheorie. Kommentiert von Moritz Schlick und Paul Hertz", hg. v. Ecke Bonk, Springer: Wien 1998 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Recknagel, Hans. "Die Nürnbergische Universität Altdorf und ihre großen Gelehrten", Druckerei Carl Hessel: Feucht 1998 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Hansen, Frank-Peter. "G.W.F. Hegel: Wissenschaft der Logik. Ein Kommentar", Königshausen & Neumann: Würzburg 1996 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Frascolla, Pascquale. "Wittgenstein’s Philosophy of Mathematics", Routledge: London/New York 1994 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Resnik, Michael D., "Mathematics as as Science of Patterns", Clarendon Press: Oxford 1997 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Stelzner, Werner, Gottlob Frege. Jena und die Geburt der modernen Logik, ReFIT: Jena 1996 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Peckhaus, Volker, „Axiomatische Ethik“, In: Zwischen Kant und Hare: Eine Evaluation der Ethik Leonard Nelsons, hg. v. Dieter Krohn/Barbara Neißer/Nora Walter, dipa-Verlag: Frankfurt a.M. 1998, 37–61 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

van Dalen, Dirk. “The Role of Language in Brouwer’s Work”, In: Ewa Orłowska (Hg.), Logic at Work. Essays Dedicated to the Memory of Helena Rasiowa, Physica-Verlag: Heidelberg 1999, 3–14 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Bolzano, Bernard. "Miscellanea mathematica 12", hg. v. Bob van Rootselar/Anna van der Lugt, Frommann-Holzboog: Stuttgart-Bad Cannstatt 1999 (Bernard Bolzano-Gesamtausgabe; II.B.7.2) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Bolzano, Bernard, "Miscellanea mathematica 14", hg. v. Bob van Rootselar/Anna van der Lugt, Frommann-Holzboog: Stuttgart-Bad Cannstatt 1999 (Bernard Bolzano-Gesamtausgabe; II.B.8.2) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Hoeltgen, Karl Josef, “Clever Doges and Nimble Spaniels: On the Iconography of Logic, Invention, and Imagination”,In: Explorations in Renaissance Culture 24 (1998), 1–36 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Anderson, C. Anthony, “Alonzo Church’s Contributions to Philosophy and Intensional Logic”, Bull. Symb. Logic 4, No. 2 (1998), 129–171 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)